Pertumbuhan Udang Galah (Macrobrachium Rosenbergii) yang Diberi Perlakuan Vegetable Floating Raft (VFR) - Siti Maria; Novita MZ; Arif Supendi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Galah shrimp is one type of freshwater shrimp that has great potential for cultivation. One of the obstacles to the growth of king prawns is water quality. This study was conducted to determine the effect of the installation of Vegetable Floating Raft (VFR) on the growth of king prawns (Macrobrachium rosenbergii). This study was conducted using the t-test method, with control and Vegetable Floating Raft treatments. The results showed that the growth pattern of weight and length of king prawns in each treatment was relatively the same. However, the daily weight growth rate of king prawns in the control treatment was greater at 3.36%, compared to the treatment of Vegetable floating raft at 1.26%, while the daily length growth rate of king prawns in the control treatment was 0.86%. The daily length growth rate in the Vegetable floating raft treatment was smaller at 0.61%. During the study the value of the degree of survival of the control treatment was 95%, while in the treatment of Vegetable floating raft the percentage of the degree of survival of king prawns was 62%. Based on the results of visual observations seen the rest of the feed and the rest of the skin during molting. It is suspected that shrimp are stressed due to changes in water quality characterized by increased ammonia levels in the last maintenance week caused by the death of kale plants in the maintenance medium.